Study on Localized Scleroderma, Associated with Lyme Disease - Shkilna, Mariia; Shtokailo, Kateryna; Ivakhiv, Oleh; Humenna, Roksolana; Huk, Mariana; Petruk, Alina; Smahlii, Zoriana (New Frontiers in Medicine and Medical Research Vol. 10, 2021)
Localized scleroderma (morphea) is a long-term progressive chronic disease characterised by a connective tissue lesion in the skin with a predominance of fibro-sclerotic and vascular problems. The present studies based on 40 patients, which conducted a questionnaire and laboratory examination. The age of tested persons ranged from 18–74years. Because of the skin thickness, the index of the severity of localised scleroderma associated with Lyme disease was lower than in responders alone with morphea. As a result, the topic of our research demands more attention from dermatologists not only from Ukraine, but from all around the world.